Reconsider the Meaning of Scapegoat Ritual in Leviticus 16:20-22 - Loba, Klementius Anselmus; Aryanto, Antonius Galih Arga Wiwin; Tanureja, Vincentius Indra Sanjaya (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2025)
The scapegoating ritual in Leviticus 16 is central to ancient Jewish religion as part of the Yom Kippur celebration. The sacrifice of a scapegoat thrown into the desert is a unique ritual because it only appears in Leviticus 16 of the entire biblical text, and the only story that uses an animal to take away all the sins of the Israelites. The issue that will be discussed in this study is to find the origins and meaning of this ritual. From the historical criticism interpretation approach to the text of Leviticus 16:20-22, it can be concluded that the meaning of this ritual can be used as a warning (threat) for the Israelites, in which expulsion/exile is a real possibility if they live in sin, and also as a means (ceremony) to reconcile God and man.